Curiosity - Manguel, Alberto (New Haven Yale University Press, 2015)
"Curiosity has been seen through the ages as the impulse that drives our knowledge forward and the temptation that leads us toward dangerous and forbidden waters. The question "Why?" has appeared under a multiplicity of guises and in vastly different contexts throughout the chapters of human history. Why does evil exist? What is beauty? How does language inform us? What defines our identity? What is our responsibility to the world? In this book, Alberto Manguel's most personal work to date, the author tracks his own life of curiosity through the books that have mapped his way. Manguel chooses as his guides a selection of writers who sparked his imagination in new directions. He dedicates each chapter to a single thinker, scientist, artist, or other figure who demonstrated in a fresh way how to ask "Why?" Leading us through a full gallery of inquisitives, among them Thomas Aquinas, David Hume, Lewis Carroll, Rachel Carson, Socrates, and, most importantly, Dante, Manguel affirms how deeply connected our curiosity is to the readings that most astonish us, and how essential to the soaring of our own imaginations"--Provided by publisher.
Includes bibliographical references (pages 329-361) and index.
Keywords: Manguel, Alberto -- Books and reading; Literature -- Appreciation